Comparison of IL-6 and TNF-Alfa Serum Levels in Pre and Post Radiotherapy Nasopharyngeal Carcinoma Patients at the NTB Provincial Hospital - Wina Annisa, Alifia (Jurnal KESANS : Kesehatan dan Sains, 2021)
Nasopharyngeal carcinoma is often found in Asia, especially in South and Southeast China, with Indonesia being the fourth most common malignancy after breast cancer, cervical cancer, and lung cancer. NPC can generally be diagnosed only in the late stages, so it can increase morbidity and mortality. One of the recommendations for therapy for NPC is radiotherapy, but radiotherapy still fails due to a chronic inflammatory process involving several inflammatory cytokines such as IL-6 and TNF-Alfa. Cytokines play a role in various signaling pathways that can lead to increased proliferation, migration, invasion, angiogenesis, and inhibit apoptosis and even have an effect on resistance to therapy in many cancer cells, especially NPC.  A good understanding of this pro-inflammatory cytokine, is expected to improve the prognosis in NPC patients in the future, knowing serum levels of IL-6 and TNF-Alfa pre and post radiotherapy. This is a preliminary study or literature study before the main study is conducted. Sources include scientific journals accessed through an online portal, namely NCBI. Poor prognosis in NPC patients with high serum levels of IL-6 and TNF-Alfa. The higher the levels of IL-6 and TNF-Alfa in post-radiotherapy NPC patients, the worse the condition is because these pro-inflammatory cytokines can activate various signaling pathways.